2018
DOI: 10.1186/s12877-018-0845-9
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity and reliability of the Community Balance and Mobility scale in young-older adults

Abstract: BackgroundWith the growing number of young-older adults (baby-boomers), there is an increasing demand for assessment tools specific for this population, which are able to detect subtle balance and mobility deficits. Various balance and mobility tests already exist, but suffer from ceiling effects in higher functioning older adults. A reliable and valid challenging balance and mobility test is critical to determine a young-older adult’s balance and mobility performance and to timely initiate preventive interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 46 publications
(100 reference statements)
2
40
0
Order By: Relevance
“…The high function of our study group probably explains the inability of the FRT and TUG to differentiate between fallers and non-fallers. However, despite being high functioning, 14.8% of the people had experienced a fall within the past year, a finding which is consistent with the rate of fall previously reported in healthy and high-functioning elderly individuals (16,29). Of note, the Unstable Board Balance Test reliability discriminated between fallers and non-fallers, and this in the absence of any self-reported difficult with walking.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high function of our study group probably explains the inability of the FRT and TUG to differentiate between fallers and non-fallers. However, despite being high functioning, 14.8% of the people had experienced a fall within the past year, a finding which is consistent with the rate of fall previously reported in healthy and high-functioning elderly individuals (16,29). Of note, the Unstable Board Balance Test reliability discriminated between fallers and non-fallers, and this in the absence of any self-reported difficult with walking.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that dynamic balance tests could be more appropriate than the BBS and TUG to differentiate the risk of falls among healthy, active, elderly individuals (15,16). Thus, we developed the Unstable Board Balance Test for this purpose, anticipating that it would not be limited by the same ceiling effect of BBS or TUG in this population.…”
mentioning
confidence: 99%
“…Functional performance was measured using Timed-Up-and-Go test [35]). The Community Balance and Mobility Scale (CBMS) was used to measure balance and mobility in 13 challenging tasks representing functional skills required for safe ambulation in relatively fit seniors [36]. Aerobic capacity was measured using the 400 m walk at a fast pace (20 times in a 20 m loop).…”
Section: Methodsmentioning
confidence: 99%
“…The Community Balance and Mobility Scale (CBMS) has recently been identified as a valid, reliable and comprehensive performance-based assessment for measuring physical function in seniors [2,4]. It contains a range of challenging balance and physical tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This limits its feasibility for use in large-scale public health approaches [5], or in daily clinical practice. While difficult to administer, the CBMS can be considered a more sensitive and appropriately challenging test of gait, balance and mobility as compared to other tests more commonly used in seniors [2,4,6].…”
Section: Introductionmentioning
confidence: 99%